Synthesis and properties of thin-film polyvinyl alcohol composite membranes. - Lang, Kangmin. (University of Ottawa (Canada), 1993)
Thin-film composite (TFC) membranes were developed with a polysulfone UF membrane used as the microporous substrate, polyvinyl alcohol as the material for skin layer formation and malic acid as the cross-linking agent. The cross-linking reactions of the membrane skin layer were carried out at high or ambient temperatures, and at the interface by using two miscible or immiscible solvents. Various parameters involved in the TFC membrane-making process have been investigated, and the flux change corresponding to individual steps in the membrane-making process was identified. The membrane transport properties and surface characteristics were studied by exposing membranes to chlorine test, by determining separations for various inorganic electrolyte and organic solutes, and by measuring ion-exchange-capacity. Separation experiments revealed the negatively charged feature of the PVA TFC membrane surface. Further, liquid chromatography was introduced to study the interfacial interaction forces working between membrane and solute in the membrane system. The TFC PVA membranes developed in this work can be classified into reverse osmosis membranes and nanofiltration membranes. The former class of membranes exhibits sodium chloride separation of 90% and product rate of 14 g/10 cm$\sp2$.h when the feed sodium chloride concentration and operating pressure are 2000 ppm and 1724 kPag, while the latter class of membranes exhibits sodium chloride separation of 70% and product rate of 45 g/10 cm$\sp2$.h at the operating pressure of 1550 kPag.
Keywords: Engineering, Chemical.